2020
DOI: 10.1016/j.imu.2020.100458
|View full text |Cite
|
Sign up to set email alerts
|

Applying computer simulations in battling with COVID-19, using pre-analyzed molecular and chemical data to face the pandemic

Abstract: Coronavirus disease 2019 (COVID-19) has made many concerns for healthcare services especially, in finding useful therapeutic(s). Despite the scientists’ struggle to find and/or creating possible drugs, so far there is no treatment with high efficiency for the disease. During the pandemic, researchers have performed some molecular analyses to find potential therapeutics out of both the natural and synthetic available medicines. Computer simulations and related data have shown a significant role in drug discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The antiviral activities of natural products and herbs are been extensively studied and are proven to show the remarkable activity against coronavirus [ [18] , [19] , [20] , [21] ]. Hence, keeping in mind the current situation we have focussed on various classes of the compound such as antiviral drugs ( abacavir, acyclovir, quinoline, hydroxyquinoline ), antimicrobial drugs ( levofloxacin, amoxicillin, cloxacillin, ofloxacin ), natural compounds ( lycorine, saikosaponin, myricetin, amentoflavone ), herbal compounds ( silymarin, palmatine, curcumin, eugenin ) available in Indian Ayurveda .…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral activities of natural products and herbs are been extensively studied and are proven to show the remarkable activity against coronavirus [ [18] , [19] , [20] , [21] ]. Hence, keeping in mind the current situation we have focussed on various classes of the compound such as antiviral drugs ( abacavir, acyclovir, quinoline, hydroxyquinoline ), antimicrobial drugs ( levofloxacin, amoxicillin, cloxacillin, ofloxacin ), natural compounds ( lycorine, saikosaponin, myricetin, amentoflavone ), herbal compounds ( silymarin, palmatine, curcumin, eugenin ) available in Indian Ayurveda .…”
Section: Introductionmentioning
confidence: 99%
“…Previous in silico studies and molecular analysis of different CoVs showed the potential antiviral effects of phytochemicals at different stages of viral biogenesis, including binding to ACE2, surface gangliosides, RdRp, viral spike protein, and viral protease in host cells and paved the way for more clinical and experimental studies [ 9 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Nevertheless, it should be considered that an acceptable antiviral activity in virtual screenings does not necessarily guarantee in vivo antiviral activity, and that is why an overview of flavonoids with antiviral properties in experimental studies is a further step toward the selection of natural antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…SARS, MERS, and SARS-CoV-2 are all RNA βCoVs. SARS-CoV-2 genome is 88% identical to bat-derived severe acute respiratory syndromes (SARS)-like CoVs, 79% similar to SARS-CoV, and 50% similar to MERS-CoV [ 8 , 9 ]. SARS-CoV-2 proteins are 90%–100% homologous to SARS-CoV; though, orf10 and orf8 are different between SARS-CoV-2 and SARS-CoV.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Similarly, a study conducted on thirteen compounds of plants in the TCM system pharmacology (TCMSP) database, discovered a compound Dihydrotanshinone I to possess high binding affinity with the viral spike protein. 22 Plants belonging to the Glycyrrhiza spp. exert various pharmacological actions and are extensively utilized in the TCM system.…”
Section: Discussion Phytochemicals As Candidates To Target Spike Proteinmentioning
confidence: 99%